Sporters' visual comfort assessment in gymnasium based on subjective evaluation & objective physiological response. (November 2022) - Shi, Ligang; Li, Yuqing; Tao, Lulu; Zhang, Yuanxue; Jiang, Xintong; Yang, Zhaojing; Qi, Xinzhu; Qiu, Jinghan
Abstract: Visual comfort is affected by the light environment of interior spaces. However, relatively few studies have combined subjective and objective indicators of visual comfort in the assessment of indoor sport facilities. Thus, the purpose of this was to determine the factors influencing visual comfort and establish corresponding thresholds by combining subjective evaluation, objective physiological indicators, and photometric light environment assessment. The experiment was conducted at a university gymnasium in Harbin, located in the northeast of China, during summer, autumn, and winter. The visual comfort of the participants was assessed via subjective evaluation via questionnaires, and objective physiological indicators were recorded using biosensors. Additionally, high-dynamic-range images were used to assess the light environment. Subjective evaluation revealed that visual comfort was affected by the glare intensity, target clarity, and emotional state. Objective physiological indicators showed that emotional arousal and alertness were higher in autumn and winter than in summer. Furthermore, the physiological indicators and subjective evaluation of visual comfort were highly consistent with each other. In summer, acceptable ranges of the luminance ratio of the window area to the field of view were less than 5 and greater than 10, and comfortable ranges were less than 3 and greater than 12. In winter, the upper acceptable and comfortable thresholds were 42 and 13, respectively. This study provides a reference point for optimizing gymnasium light environment design. Highlights: Subjective, objective, and environmental indicators of visual comfort were combined. Objective physiological indicators of visual comfort were measured using biosensors. Glare and emotional state most influenced subjective visual comfort evaluation. Physiological indicators and subjective evaluations were consistent with each other. Luminance thresholds of visual comfort were proposed.